Acute Effects of Pedaling Cadence at Low Intensity on Arterial Stiffness in Healthy Young Men - Yin, Jun; Wu, Hao; Yu, Lan; Zhang, Jing; Zhu, Weili (International Journal of Sports Medicine, 2019)
To examine the acute influence of pedaling cadence on arterial stiffness in young men, 15 healthy men (21.8±0.4 years) underwent 3 trials in self-control crossover design: non-cycling control (CON), cycling at 60 (RPM60) and 90 rounds per min (RPM90). Cycling lasted 30 min at intensity of 35% heart rate reserve. Arterial stiffness in cardio-ankle vascular index (CAVI) was measured at baseline (BL), immediately after (0 min) and 40 min after cycling. There were no significant CAVI changes over time in CON. CAVI in RPM60 decreased immediately after exercise and returned to baseline afterwards (6.1±0.2, 5.6±0.2 and 6.0±0.2 at BL, 0 and 40 min, respectively). RPM90 elicited significant CAVI reduction from 6.2±0.2 at BL to 5.5±0.2 at 0 min, and reverted to 5.7±0.1 at 40 min, maintaining significant difference to its baseline. There was no significant CAVI difference between RPM60 and CON, whereas CAVI in RPM90 was significantly lower than that in CON at 0 min (5.5±0.2 vs 6.1±0.2, P<0.01) and 40 min (5.7±0.1 vs 6.3±0.1, P<0.05). Despite equivalent exercise volume, arterial stiffness improvement induced by cycling was influenced by pedaling cadence. Higher cadence resulted in superior effect on arterial stiffness.
Keywords: pedaling cadence; low-intensity cycling; arterial stiffness